Cars Online Catalog Based Management Relationship Partner On Hermasari Motor - Muhammad Rifki Ariady; Antok Supriyanto; Tan Amelia (Jurnal Sistem Informasi Universitas Dinamika, 2018)
Hermasari Motor is a showroom of buying and selling a used car that is the beginning of standing at Jl. A. Yani Km. 4,500 Banjarmasin South Kalimantan and is now at Jl. A. Yani Km. 9,100. At the beginning stood Hermasari Motor can only accommodate 10 cars and now Hermasari Motor can accommodate 35 cars. Motor Hermasari turnover obtained about 1-2 billion per month. Problems faced Hermasari Motor is the customer does not buy a car because cars that customers want are not available and the alternative offered by the car showroom is not in accordance with customer requirements, customer consequently go straight to another showroom. Own car showroom recorded data for desired customers but not available in the showroom. The showroom owner buys and holds the car in the showroom, because too many requests from customers so cars must have a broader area. To menaggulangi the problems above, the Showroom has widen the land, but have not been effective due to the widening of the land cost is very high.The solution to overcome the problems experienced by owners of the showroom is to relationship management, marketing, and online catalogs. Management of relationships with partners to establish cooperation with partners. With the cooperation showroom informed car owned partner. With this information, the showroom has a stock of more cars without having to put the car in the showroom. Showroom does not require a large area to accommodate all the cars. Marketing for determining the selling price of the Hermasari Motor cars and Partner thus gaining profit. The online catalog contains Hermasari Motor cars and partners to increase the reach of the market in car sales Hermasari Motor.After doing the implementation and evaluation of Applications Marketing Drives Online Catalog Based Client Relationship Management at Hermasari Motor accordance with the solution. Applications are made online based so that it can expand market share, because it can be accessed anywhere and customers can see the stocks owned car showroom without having to showroom. Applications can management relationship between the showroom with a partner. With the partnerships, Hermasari Motor obtain car information into the stock car Hermasari Motor so it does not require widening of the land. Applications can increase turnover and profits without the use of capital, because the showroom to get a car turnover without having to buy in advance and the price is determined by the car showroom that benefit. Applications can report selling car based on transaction history, so that the party could provide the showroom and the car more. Applications can establish communication between the showroom with partners or customers, so as to find out their needs.